Recent trends in climate of Bangalore (MAUSAM, 2002)
The linear trends in the monthly, seasonal and annual mean maximum temperature, minimum temperature, average temperature, diurnal range of temperature, rainfall, relative humidities at 0830 & 1730 hr IST of Bangalore city and airport have been analysed based on the data for the period from 1960-95. The variation in surface wind over Bangalore during above period has also been studied to find out impact of urbanisation on weather parameters. It is found that Bangalore city is becoming warmer in terms of mean maximum & mean minimum temperatures. Rate of increase is significantly higher over Bangalore city (central observatory) than that over airport during winter months. Similarly the rising trend of average temperature of Bangalore city is higher than of Bangalore airport during October to April being significantly so during winter season. Also the diurnal range of temperature of Bangalore is becoming larger in winter months with the rising trend being higher over Bangalore city than over airport. Even though rainfall does not show any significant trend, the rising trend during monsoon & falling trend during post monsoon season over Bangalore city are higher than that of Bangalore airport. Also though both Bangalore city & airport show maximum rising trend in mean relative humidity at 0830 hr IST during winter, the rate of rise is less over Bangalore city. Similarly though the relative humidity at 1730 hr IST shows decreasing trend during all the seasons, the rate of decrease is less over Bangalore city for all seasons except post monsoon season. The mean maximum, minimum and average temperatures and relative humidities show cyclic variation of their monthly trend coefficients during the year.